Pengembangan Game Edukatif Berbasis Wordwall untuk Meningkatkan Keaksaraan Anak Kelompok B - Ramadhani, Intan Sari; Gunawan, Gunawan; Astini, Baik Nilawati; Fahruddin, Fahruddin (Indonesian Publication Center, 2025)
The use of technology-based media in early childhood literacy learning remains limited, necessitating innovative approaches that support engaging and effective learning processes. This study aims to develop and assess the feasibility and effectiveness of a Wordwall-based educational game in improving the literacy skills of Group B children. The research employed a Research and Development (R&D) approach using the ADDIE model and was conducted at PAUD Al-Hijrah, West Lombok, involving 18 Group B children as subjects. The research steps included needs analysis, media design, expert validation, limited trials, and effectiveness evaluation through pre-tests and post-tests. Data collection techniques involved observation, expert validation questionnaires (media and content), and literacy tests. Validation results indicated that the media was highly feasible, with scores of 100% from media experts and 95% from content experts. Effectiveness testing showed an increase in the average score from 72.31 to 93.08, with an N-Gain score of 0.78, categorized as high. The literacy indicator with the highest improvement was recognizing the initial letter of object names, identifying letter symbols, and understanding the relationship between letter sounds and their written forms. Based on these findings, it can be concluded that the Wordwall educational game is effective and feasible for enhancing literacy skills in Group B.